Wood Occupations - Brett, Peter (Cheltenham : Nelson Thornes, 2003)
This textbook is designed for all those working or undergoing training in a wood based occupation. Written to cover the QCA accredited CITB specifications for NVQ level 1 this book provides a step by step approach and includes extensive coverage of all the underpinning knowledge required.
Keywords: Carpentry; Carpentry -- Problems, exercises, etc; Joinery; Joinery -- Problems, exercises, etc; House and Home